If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + a)(1 + b) = c Multiply (1 + a) * (1 + b) (1(1 + b) + a(1 + b)) = c ((1 * 1 + b * 1) + a(1 + b)) = c ((1 + 1b) + a(1 + b)) = c (1 + 1b + (1 * a + b * a)) = c (1 + 1b + (1a + ab)) = c Reorder the terms: (1 + 1a + ab + 1b) = c (1 + 1a + ab + 1b) = c Solving 1 + 1a + ab + 1b = c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 1a + ab + -1 + 1b = -1 + c Reorder the terms: 1 + -1 + 1a + ab + 1b = -1 + c Combine like terms: 1 + -1 = 0 0 + 1a + ab + 1b = -1 + c 1a + ab + 1b = -1 + c Add '-1b' to each side of the equation. 1a + ab + 1b + -1b = -1 + -1b + c Combine like terms: 1b + -1b = 0 1a + ab + 0 = -1 + -1b + c 1a + ab = -1 + -1b + c Reorder the terms: 1 + 1a + ab + b + -1c = -1 + -1b + c + 1 + b + -1c Reorder the terms: 1 + 1a + ab + b + -1c = -1 + 1 + -1b + b + c + -1c Combine like terms: -1 + 1 = 0 1 + 1a + ab + b + -1c = 0 + -1b + b + c + -1c 1 + 1a + ab + b + -1c = -1b + b + c + -1c Combine like terms: -1b + b = 0 1 + 1a + ab + b + -1c = 0 + c + -1c 1 + 1a + ab + b + -1c = c + -1c Combine like terms: c + -1c = 0 1 + 1a + ab + b + -1c = 0 The solution to this equation could not be determined.
| 6x+6-4x=16-x | | -.22(-n+.33)=.22n-.55 | | -100+200= | | 1.66s=5+1.5-.25 | | (-1/2u^-3/2)(-2x) | | ln(x-3)=-8 | | 4/9=y-2:5 | | 1.66s=5 | | -100m+200m= | | 2(x+1)+3(x+5)=52 | | cos(1.6x)=0 | | 5x-3(4x-6)=-8 | | -2c-3x=-3 | | -4/13-8/13 | | 3x+5+6-10x+6= | | x+(x*0.15*14)=944 | | 7x+3-2x+1-4x=17 | | 3ln(4x+4)=20 | | -3=-9-2b | | -5x+15=-22 | | 5=-7-2a/3 | | 4x+5-x-1=34 | | 4x-11y-44=0 | | 3(x+9)-20= | | -3x-2c=-3 | | 4-2z=-16 | | 12y-3=45 | | 12y-4=45 | | (4x+7)=4x-25 | | 4x-2+8x-6=-56 | | x+(x*0.15*14)=1116 | | y^2+144-400=0 |